THE ADVENTITIOUS CONSTITUENT IN FOREST PHYTOCOENOSES OF FOREST-STEPPE OF UKRAINE - Bondaruk, M. A.; Tselishchev, O. G. (Forestry and Forest Melioration, 2018)
Introduction The article analyzes a problem of the progressive development of Ukrainian flora adventization and addresses the issues in the inventory of adventitious species diversity and monitoring of their populations. We also investigated phytoinvasions in forest phytocoenoses. An adventitious floristic element is represented by 830 species of vascular plants (including 18 % archeophytes and 82 % kenophytes), about 100 species of which are highly invasive. The aim of the research was to evaluate research methods for analyzing the contamination in forest phytocoenoses by non-native higher vascular plants in Forest-Steppe and to work out and organize a systematic monitoring of phytoinvasion in forest phytocoenoses within all zones in plain parts of Ukraine. Materials and Methods The objects of research are first level monitoring plots (642 plots) located within all regions of the forest-steppe plain part of Ukraine. According to the provisions of the Global and European Development Strategies on the necessity to control the invasion and introduction of non-native adventitious species in natural and synantropized habitats (the process of neophitization), as well as to introduce a monitoring of their abundance and distribution, we analyzed the contamination of forest phytocoenoses with non-native species of vascular plants, namely their abundance – coverage and participation in the vegetation composition, distribution, distributional patterns within administrative regions of the forest-steppe zone. In addition, we tested the methodological approaches to the identification of adventitious and highly-invasive species (Mosyakin S. L., Fedoronchuk M. M. Vascular plants of Ukraine. A nomenclatural checklist, 1999) and calculated indices for adventization A (percentage of adventitious species to the total number of species) and for forest flora modernization M (percentage of kenophytes and eukenophytes in the adventitious element of flora). Furthermore, all species were classified by groups depending on the time they were introduced to the territory of Ukraine (archeophytes, kenophytes, eukenophytes). It was carried out according to the Geographical and Historical Classification of Synanthropic Vegetation by Kornas (Korna? J., 1968). Results The adventitious fraction of forest flora within monitoring plots is represented by 42 species (25 kenophytes and 17 archeophytes), one-third of which (14 species) are highly invasive and potentially dangerous species. The adventitious component of tree and shrub layer consists of 16 kenophytes (4 species are highly invasive), low shrub-grass-moss layer – 17 archeophytes (7 species are highly invasive) and 9 kenophytes (3 species are highly invasive). Adventization index of flora (10.5%) and low shrub-grass-moss layer (7.4%) of forest phytocoenoses within the forest-steppe zone is lower in comparison with the same index for the flora of Ukraine in total (14.0%). Adventization index of species composition of tree and shrub layer (29.6%) indicates the disturbance of the coenotic structure of forest communities and the deterioration in their condition. Modernization indices (M) of adventitious flora in forest phytocoenoses (59.5%) and low shrub-grass-moss layer (34.6%) are lower as compared with the similar index for the flora of Ukraine in total (82.0%). Stepped-up pace of modernization of the adventitious constituent of tree and shrub layer (100.0%) is the result of the introductory activity during artificial reforestation. Such species as Robinia pseudoacacia L., Quercus borealis Michx., Impatiens parviflora DC. and Erigeron canadensis L. are the greatest threat to phytodiversity of forests in the forest-steppe zone. Conclusions The research methods for analyzing the contamination in forest phytocoenoses with non-native species of vascular plants can be recommended to monitor the phytoinvasions in forest phytocoenoses (every 3-5 years) in all natural zones in the plain part of Ukraine. 1 Table, 15 Refs.